Late Glacial-Holocene climate variability at the south-eastern margin of the Aegean Sea - Triantaphyllou, M.V.; Ziveri, P.; Gogou, A.; Marino, G.; Lykousis, V.; Bouloubassi, I.; Emeis, K.-C.; Kouli, K.; Dimiza, M.; Rosell-Melé, A.; Papanikolaou, M.; Katsouras, G.; et al. (Marine Geology, 2009)
New micropaleontological, palynological, and geochemical results from a relatively shallow (∼500 m) sediment core (NS-14) in the south-eastern Aegean Sea provide a detailed picture of the regional expression of sapropel S1 formation in this sub-basin of the eastern Mediterranean Sea. Specifically, freshwater input during ∼10.6–10.0 ka BP has preceded the deposition of S1. Further decrease in surface water salinity is evidenced between 10.0 and 8.5 ka BP at the lower part of S1a, which in respect to S1b, is featured by warmer (∼19.5 °C) and more productive surface waters associated with dysoxic bottom conditions. A series of coolings detected within the S1 depositional interval, may be linked to outbursts of cold northerly air masses and relevant pulses in the deep-intermediate water ventilation that caused the S1 interruption between 7.9 and 7.3 ka BP and culminated during the deposition of S1b, with the decline of deep chlorophyll maximum (DCM) at ∼6.5 ka BP. The climate instability and the relevant absence of anoxia weakened the organic matter preservation in the shallow south-eastern Aegean margin during the S1 times. NS-14 record provides evidence for a distinct mid Holocene warm (up to ∼25 °C) and wet phase associated with the deposition of the sapropel-like layer SMH (Sapropel Mid Holocene), between 5.4 and 4.3 ka BP. The SMH layer could represent evidence of on-going, albeit weak, African monsoon forcing, only expressed at the south-eastern edge of the Aegean Sea. Its end is associated with the 4.2 ka BP Northern Hemisphere megadrought event and the termination of the African Humid Period at 3.8 ka BP.